2013
DOI: 10.1177/1420326x13480373
|View full text |Cite
|
Sign up to set email alerts
|

On Associations between Housing Characteristics, Dampness and Asthma and Allergies among Children in Northeast Texas

Abstract: A cross-sectional study on the home environment and children's health in Northeast Texas was carried out in [2008][2009]. Two thousand eight hundred and nineteen (2,819) parents of children (1-8 years) reported their housing characteristics, home interior surface materials, dampness and children's health status. The response rate was 71%. Health outcomes studied were wheeze, dry cough, rhinitis, eczema in the last 12 months and diagnosed asthma and hay fever. Dampness was significant risk factor for wheeze and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 33 publications
1
35
1
Order By: Relevance
“…Six home dampness‐related indicators, namely visible mold, damp stains, water damage, damp clothing/bedding, mold odor, and condensation on the inner windowpane in winter, were analyzed. The questions about dampness are similar to those of the ALLHOME study (Naydenov et al., ), the DBH study (Bornehag et al., ), Texas in America (Sun and Sundell, ), and CCHH studies in other China cities (Qu et al., ; Wang et al., ,b; Zhang et al., ,b; Zhao et al., ). The questionnaire used for CCHH Phase one is shown in the Table S5 of the CCHH summary article (Zhang et al., ).…”
Section: Methodsmentioning
confidence: 82%
See 2 more Smart Citations
“…Six home dampness‐related indicators, namely visible mold, damp stains, water damage, damp clothing/bedding, mold odor, and condensation on the inner windowpane in winter, were analyzed. The questions about dampness are similar to those of the ALLHOME study (Naydenov et al., ), the DBH study (Bornehag et al., ), Texas in America (Sun and Sundell, ), and CCHH studies in other China cities (Qu et al., ; Wang et al., ,b; Zhang et al., ,b; Zhao et al., ). The questionnaire used for CCHH Phase one is shown in the Table S5 of the CCHH summary article (Zhang et al., ).…”
Section: Methodsmentioning
confidence: 82%
“…Recently, the Shanghai group of CCHH reported that early furred pet‐keeping (Huang et al., ) and parental smoking (Liu et al., ) were risk factors for asthma and allergies among preschool children. Many studies have shown that dampness‐related problems (as evidenced by such signs as visible mold, visible damp stains, condensation on windows, and perceived mold odor) in the residence are significant risk factors for asthma and asthma‐related symptoms among children (Bornehag et al., , ; Fisk et al., ; Jaakkola et al., ; Mendell et al., ; Peat et al., ; Quansah et al., ; Sun and Sundell, ; Tischer et al., ; Weinmayr et al., ) and adults (Blanc et al., ; Brunekreef, ; Gunnbjörnsdottir et al., ; Norbäck et al., ). Bornehag et al., () have concluded that dampness in buildings appears to increase the risk of health effects (dry cough, wheeze, and asthma), especially in children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies carried out mainly in United States have shown that low income groups are exposed to high indoor pollutants and contaminants, (Chuang et al, 1999;Shapiro et al, 1999) for the above mentioned reasons. Chronic exposure to damp in dwellings is associated with important health risks and mainly respiratory problems as asthma and allergies, (Sun and Sundell, 2013). Studies carried out in Ireland, (Healy and Clinch, 2004) showed that almost 50% of those having a dampness problem reported that are under fuel poverty conditions.…”
Section: Indoor Pollution and Healthmentioning
confidence: 98%
“…1 In recent years, the prevalence of childhood eczema has rapidly increased worldwide. [2][3][4][5][6] Between 1992 and 1998, the International Study of Asthma and Allergies in Childhood (ISAAC) conducted a survey of 700 000 children from 56 countries on eczema and other allergic diseases and found that the prevalence of eczema in children was 0.3%-20.5%. 7,8 In some developed countries, approximately 15%-30% of children and 2%-10% of adults have eczema.…”
Section: Introductionmentioning
confidence: 99%